Developing theology for evolution - Wiltsher, Chris (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
This speculative paper explores one idea for approaching some of the problems which arise when the doctrines of Christian theology meet the current scientific understanding of evolution through natural selection. The main suggestion is that Christian theology should relax the requirement that God controls everything. Some implications of this move are explored, with a brief look at how similar ideas might be of use for non-Christian religions entering into dialogue with the theory of evolution
Keywords: chaos; divine control; evolution; theology